Research and Design of Toy Chinese Dragon Model based on OpenSCAD and Render based on Three.js - Zhu, Jiaqi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Nowadays, there are a lot of 3D models in the world, but how to build a Chinese Dragon is relatively few methods.Aiming at this problem, this paper put forward a method which made up for the deficiency in this aspect. In order to build this model, OpenSCAN software was used in this paper. This paper also divided Chinese Dragon into four parts: head, body, claws and tail, and used different methods to model these four parts. At the same time, in order to make the Chinese Dragon look more realistic, this paper also implemented basic lighting and shadows on Three.js. The methods used are the Phong model and shadow maps. What’s more, In order to achieve the dragon in Chinese people’s imagination, this paper also simulated the appearance of dragons breathing fire and surround fire. In the process of doing this, in order to make the effect of fire more realistic, this paper used Perlin noise to simulate the burning of fire. Meanwhile, in order to compare the effects of different surround fires, some people were invited to evaluate the effects of various surround fires. For the final experimental results, a cartoon style Chinese Dragon was made, and the fire effect was achieved very well.